Genetic Manipulation of Biosynthetic Pathways in Mint - Fuchs, Lorenz K.; Holland, Alistair H.; Ludlow, Richard A.; Coates, Ryan J.; Armstrong, Harvey; Pickett, John A.; Harwood, John L.; Scofield, Simon (Frontiers in Plant Science, 2022)
In recent years, the study of aromatic plants has seen an increase, with great interest from industrial, academic, and pharmaceutical industries. Among plants attracting increased attention are the Mentha spp. (mint), members of the Lamiaceae family. Mint essential oils comprise a diverse class of molecules know as terpenoids/isoprenoids, organic chemicals that are among the most diverse class of naturally plant derived compounds. The terpenoid profile of several Mentha spp. is dominated by menthol, a cyclic monoterpene with some remarkable biological properties that make it useful in the pharmaceutical, medical, cosmetic, and cleaning product industries. As the global market for Mentha essential oils increases, the desire to improve oil composition and yield follows. The monoterpenoid biosynthesis pathway is well characterised so metabolic engineering attempts have been made to facilitate this improvement. This review focuses on the Mentha spp. and attempts at altering the carbon flux through the biosynthetic pathways to increase the yield and enhance the composition of the essential oil. This includes manipulation of endogenous and heterologous biosynthetic enzymes through overexpression and RNAi suppression. Genes involved in the MEP pathway, the menthol and carvone biosynthetic pathways and transcription factors known to affect secondary metabolism will be discussed along with non-metabolic engineering approaches including environmental factors and the use of plant growth regulators.